Correlation of Electron Beams and Hard X‐ray Emissions in ISTTOK Tokamak. Issue 9 (November 2013) - Jakubowski, L.; Plyusnin, V.V.; Malinowski, K.; Sadowski, M.J.; Zebrowski, J.; Rabiński, M.; Fernandes, H.; Silva, C.; Duarte, P.; Jakubowski, M.J.
Abstract The paper reports on experimental studies of electron beams in the ISTTOK tokamak, those were performed by means of an improved four‐channel detector. The Cherenkov‐type detector measuring head was equipped with four radiators made of two types of alumina‐nitrate (AlN) poly‐crystals: machinable and translucent ones, both of 10 mm in diameter and 2.5 mm in thickness. The movable support that enabled the whole detectors to be placed inside the tokamak vacuum chamber, at chosen positions along the ISTTOK minor radius. Since the electron energy distribution is one of the most important characteristics of tokamak plasmas, the main aim of the study was to perform estimations of an energy spectrum of the recorded electrons. For this purpose the radiators were coated with molybdenum (Mo) layers of different thickness. The technique based on the use of Cherenkov‐type detectors enabled the detection of fast electrons (of energy above 66 keV) and determination of their spatial and temporal characteristics in the ISTTOK experiment. Measurements of hard X‐rays (HXR), which were emitted during ISTTOK discharges, have also been performed. Particular attention was paid to the correlation measurements of HXR pulses with run‐away electron beams. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)